2013
DOI: 10.1590/s1677-54492013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb vascular dysfunction in cyclists

Abstract: Sports-related vascular insufficiency affecting the lower limbs is uncommon, and early signs and symptoms can be confused with musculoskeletal injuries. This is also the case among professional cyclists, who are always at the threshold between endurance and excess training. The aim of this review was to analyze the occurrence of vascular disorders in the lower limbs of cyclists and to discuss possible etiologies. Eighty-five texts, including papers and books, published from 1950 to 2012, were used. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…A recent review of the human literature assessing sports‐related vascular insufficiency in cyclists supports the theory of alterations in haemodynamics, postulating that the main aetiological factor is mechanical strain secondary to posture and performance intensity (di Alencar et al . ). Lesions were commonly identified in the external and internal iliac arteries, with 81.5% (119/146) of cases being male and 18.5% (27/146) being female.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent review of the human literature assessing sports‐related vascular insufficiency in cyclists supports the theory of alterations in haemodynamics, postulating that the main aetiological factor is mechanical strain secondary to posture and performance intensity (di Alencar et al . ). Lesions were commonly identified in the external and internal iliac arteries, with 81.5% (119/146) of cases being male and 18.5% (27/146) being female.…”
Section: Discussionmentioning
confidence: 97%
“…It is also suggested that a combination of the repetitive movements and vascular compression causes the endothelium to convert from an antithrombogenic to a prothrombotic state, resulting in the production of fibronectin and von Willebrand factor (di Alencar et al . ). Unlike the horse, the primary lesion is endofibrotic stricture of vessels, which can cause secondary arterial thrombosis if severe.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation